2016
DOI: 10.18632/oncotarget.12050
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome loss and the pseudoautosomal region genes in hematological malignancies

Abstract: Cytogenetic aberrations, such as chromosomal translocations, aneuploidy, and amplifications, are frequently detected in hematological malignancies. For many of the common autosomal aberrations, the mechanisms underlying their roles in cancer development have been well-characterized. On the contrary, although loss of a sex chromosome is observed in a broad range of hematological malignancies, how it cooperates in disease development is less understood. Nevertheless, it has been postulated that tumor suppressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 110 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…Patient case 2 featured the highest number of losses on chromosomes 1, 14, 19, 21, and a partial loss of chromosome 7. The sex chromosome loss suggests an involvement of pseudo autosomal regions, which have been the prime candidates for harboring tumor suppressors [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patient case 2 featured the highest number of losses on chromosomes 1, 14, 19, 21, and a partial loss of chromosome 7. The sex chromosome loss suggests an involvement of pseudo autosomal regions, which have been the prime candidates for harboring tumor suppressors [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pioneer studies of chromosome loss in cultured lymphocytes indicated that susceptibility to loss is nonrandom. In respect to that, sex chromosomes are most susceptible, with incidence of X loss of heterozigosity in females and Y loss of heterozigosity in males rising with age (Jacobs et al, ; Jacobs et al, ; Galloway and Buckton, ; Weng et al, ). There is a basic hypothesis that states that a loss of a smaller or heterochromatin‐rich chromosome with less actively transcribed genes is more frequently missegregated since huger parts of heterochromatin between homologs may result in asynchrony in replication, which may contribute to misalignment and malsegregation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an over-abundance of 47,XXY males also develop lupus, implicating the presence of the inactive X as a risk factor for this disorder. While a full assessment of the many potential impacts of the X on [6] or with ageing [7] a See text for additional discussion and references. rstb.royalsocietypublishing.org Phil.…”
Section: (C) Sexual Dimorphismmentioning
confidence: 99%
“…Impact of genes on the inactive X. Xa, active X; Xi, inactive X; X m , maternal X; X p , paternal X; PAR, pseudoautosomal region. [6] or with ageing [7] a See text for additional discussion and references. b Imprinted genes are reported for a small number of genes in somatic tissue of mouse X but have not yet been identified on the human X. rstb.royalsocietypublishing.org Phil.…”
Section: (C) Sexual Dimorphismmentioning
confidence: 99%